SUMBANGAN AJARAN FORMATIO MARIAL ST. LOUIS MARIE DE MONTFORT BAGI PENGHAYATAN DEVOSI MARIAL DI INDONESIA - Cimi, Severinus Savio; Firmanto, Antonius Denny (Bahasa Indonesia, 2024)
This article focuses on efforts to explore the contribution of the teachings of St. Marial Formation. Louis Marie de Montfort for the appreciation of Marial devotion in Indonesia. Marial devotion is an integral part of Catholic spirituality and its appreciation is very well developed in Indonesia. However, there are quite a few people who carry out devotional practices without being accompanied by an understanding of correct Marial reflection so that the possible consequence is minimal social involvement in the concrete reality of living together in Indonesia. St. Louis Marie de Montfort is one of the theologians and mystics who offers the teaching of Marial formation as a path to correct reflection about Mary. Marial Formation is a term that refers to spiritual formation or spiritual formation which is focused on the way Mary, the mother of Jesus, believed in God. The literature method will be used in this research and the status of the questionnaire proposed is how Marial formation teachings contribute to the appreciation of Marial devotion in Indonesia. This research found that Marial formation teachings help provide a foundation for Marian devotion, provide spiritual education for devotees, and spur social involvement among Marial devotional adherents in Indonesia